2021
DOI: 10.1111/ppa.13352
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure analysis of isolates of the rice false smut pathogen Ustilaginoidea virens in India

Abstract: Genetic diversity assessment and population structure analysis are essential for characterization of pathogens and their isolates. Markers are essential tools for exploring genetic variation among the isolates. False smut of rice caused by Ustilaginoidea virens, formerly Villosiclava virens, is a major emerging disease of rice in India. A high level of variability is observed at the field level, but no information is available from India on genetic diversity and population structure. This is the first report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Only two sub‐populations, that is the maximum value of ∆K = 2 was found on analysis of RAPD and SSR obtained data. Bag, Ray, et al (2021), Bag, Basak, et al (2021) also observed two sub‐populations during the analysis of U . virens isolates collected from eastern and north‐eastern India.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Only two sub‐populations, that is the maximum value of ∆K = 2 was found on analysis of RAPD and SSR obtained data. Bag, Ray, et al (2021), Bag, Basak, et al (2021) also observed two sub‐populations during the analysis of U . virens isolates collected from eastern and north‐eastern India.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, in one study on U . virens populations from eastern and north‐eastern India have also shown 60% similarities (Bag et al, 2021; Bag, Ray, et al, 2021). Jia et al, 2015, also used 19 SSR markers for diversity analysis of 87 U .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RFS was initially identified by Cooke in 1878 in Tirunelveli, Tamil Nadu, India, and was considered a minor and sporadic disease limited to a few areas [2]. Interestingly, RFS was commonly referred to as the "Laxmi-buti" disease, symbolizing a bountiful harvest and prosperity associated with the goddess of wealth and prosperity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Rice false smut, caused by Ustilaginoidea virens (Cooke) Takah (teleomorph Villosiclava virens ) infecting rice spikelets, is currently a devastating fungal disease [ 1 , 2 , 3 , 4 ]. In recent years, the disease has occurred all over the world, and the outbreak has been more frequent and increasing year by year in rice-producing areas in China [ 5 , 6 , 7 , 8 ]. According to statistics, from 2008 to 2016, the annual average area of false smut in China reached 3.062 million hectares, resulting in an average annual yield loss of 158.6 million kilograms [ 8 ].…”
Section: Introductionmentioning
confidence: 99%